Twentieth-Century Chinese Historiography : One Hundred Years of Changes and Return of New Historiography and New Sinology - Wang, Xuedian, (Asian Studies E-Books Online, Collection 2026., 2026)
This book takes as its main thread the struggle and cyclical alternation between the New Historiography (rooted in China's narrative historical tradition) and the New Sinology (grounded in textual criticism) in modern Chinese historiography over the past century. Focusing primarily on the differing interpretations of historical scholarship's essence among various schools of historians during this period, it examines the resulting divergences in concepts, methodologies, and approaches. The work further evaluates the actual impact of these differences on the development of historical studies. This book is essential for anyone interested in the intersection of history, culture, and intellectual thought.